2017
DOI: 10.1177/1010428317717655
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of transferrin receptor-1 induces cholangiocarcinoma progression via induction of labile iron pool

Abstract: Labile iron pool is a cellular source of ions available for Fenton reactions resulting in oxidative stress. Living organisms avoid an excess of free irons by a tight control of iron homeostasis. We investigated the altered expression of iron regulatory proteins and iron discrimination in the development of liver fluke-associated cholangiocarcinoma. Additionally, the levels of labile iron pool and the functions of transferrin receptor-1 on cholangiocarcinoma development were also identified. Iron deposition was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 33 publications
2
24
0
2
Order By: Relevance
“…Our data suggested that inhibition of CD71 suppressed the self-renewal ability, cell survival after irradiation treatment, cell proliferation, and in vitro and in vivo tumorigenicity of cervical cancer cells. Downregulation of CD71 in a cholangiocarcinoma cell line with siRNA has also been reported to inhibit cell migration, proliferation, and cell survival (18), and suppression of CD71 using siRNA in ESCC cells reduces their colony-forming ability and arrests cells in the S-phase (19). In this study, we demonstrated that downregulation of CD71 in HPV16-positive SiHa cells and HPV18-E6-overexpressing 18E6-5 cells suppressed self-renewal ability and cell proliferation.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our data suggested that inhibition of CD71 suppressed the self-renewal ability, cell survival after irradiation treatment, cell proliferation, and in vitro and in vivo tumorigenicity of cervical cancer cells. Downregulation of CD71 in a cholangiocarcinoma cell line with siRNA has also been reported to inhibit cell migration, proliferation, and cell survival (18), and suppression of CD71 using siRNA in ESCC cells reduces their colony-forming ability and arrests cells in the S-phase (19). In this study, we demonstrated that downregulation of CD71 in HPV16-positive SiHa cells and HPV18-E6-overexpressing 18E6-5 cells suppressed self-renewal ability and cell proliferation.…”
Section: Discussionsupporting
confidence: 51%
“…Our findings provided additional evidence indicating that CD71 protein is highly expressed in cervical cancer. Increased expression of CD71 has also been reported in many other cancers, including astrocytic brain tumors, breast cancer, cholangiocarcinoma, ESCC, pancreatic cancer, and renal cell carcinoma (17)(18)(19)(20)(21)(22). Furthermore, enhanced CD71 expression has been reported to be correlated with poor clinical outcomes in patients with estrogen receptor-positive breast cancer and glioblastoma, suggesting that CD71 might serve as a therapeutic target (21,22).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Contribution to CCA progression and poorer clinical outcomes. [64] Ferritin high expression Negative prognostic index for CCA patients. [65] Fpn reduced mRNA levels Reduction of iron release, in tumor cells of CCA patients sample compared to matched surrounding liver, suggests that elevated iron content is a negative prognostic factor.…”
Section: Tfr1 High Expressionmentioning
confidence: 99%
“…TfR-1 knockdown has been shown to reduce iron uptake by 80% in human hepatoma cell line (Herbison et al 2009). Moreover, the aberrant expression of TfR-1 substantially contributed to the regulation of systemic iron levels and can play key roles in CCA development (Jamnongkan et al 2017). TfR-1 has been reported to be a major molecule that responded to iron uptake mediated by insulin through hypoxia conditions (Biswas et al 2013).…”
Section: Discussionmentioning
confidence: 99%